Impact Factor of Cost Using the Sensitivity Method - Challoumis, Constantinos (International journal of multicultural and multireligious understanding, 2024)
This paper is a special issue about the sensibility of taxation in the cost, that is based on the Sensitivity Method. Therefore, it has been done a study for the impact factor of the tax revenues of the countries that are tax havens subject to the trustworthiness of the tax system. From the view of how much is affected the companies that participate in controlled transactions, can obtain the impact of cost, when there is not that factor with the case that exists in the analysis of transfer pricing. It determines the behavior of the tax system subject to the cost.